Human Resource Competence, Technology Utilization, and Safety Culture on Organizational Performance through Operational Effectiveness - Susilo Susilo; Chablullah Wibisono; Sri Yanti (Goodwood Publishing, 2026)
Purpose: This study empirically examines the influence of human resource competence, technology utilization, and safety culture on organizational performance through operational effectiveness as an intervening variable at the Tanjung Uban Sea and Shipping Supervision Base (PPLP). Research Methodology: A causal quantitative design (explanatory research) was applied using a census technique across the entire population of 110 employees. Primary data were collected through a structured five point Likert questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4, including outer model and inner model evaluation with bootstrapping of five thousand subsamples. Results: Human resource competence and technology utilization significantly strengthen operational effectiveness, while safety culture shows no significant effect. None of the three exogenous variables directly affects organizational performance, yet operational effectiveness significantly and directly improves performance and fully mediates the effects of competence, technology, and safety culture on organizational performance. Conclusions: Organizational performance at this high risk maritime base is achieved not through inputs alone but through their conversion into optimal operational effectiveness. Limitations: The study is confined to one maritime supervision unit with 110 respondents and relies solely on internal employee perceptions. Contributions: The findings extend capacity building theory in high risk public sector maritime institutions by demonstrating a full mediation pattern across all input variables.